PENGARUH STRATEGI POSITIONING DAN STRATEGI DIFERENSIASI TERHADAP KEPUTUSAN PEMBELIAN DI POMELOTEL - Rani Adisti N (LPPM Universitas Asa Indonesia, 2017)
Competition in the hotel field is increasingly tight, companies are competing to create competitive marketing strategies and achieve goals. Consumers or guests who live as well as users of hotel products and services is the highest priority for companies to influence every consumer's decision to buy products and services. Different ways of embedding a company image need to be implemented with a closely related marketing strategy in positioning strategy and differentiation strategy that accentuate the difference and uniqueness of the service products offered. This study aims to analyze the effect of positioning strategy and differentiation strategy partially or simultaneously to the purchasing decision Respondents are taken purposively from the population of hotel residents, within a period of three months. Data processing is used with multiple linear analysis techniques with SPSS 3.0. The results of research that positioning strategy, and differentiation strategy correlated significantly with purchasing decisions with correlation coefficient of positioning strategy is 0.505 and the coefficient of determination is 5.50%. The value of correlation coefficient of differentiation strategy is 0.417 and the coefficient of determination is 17.39%. There is a need to improve the quality of services more acceptable and the addition of facilities such as ATM center to facilitate guests in conducting cash transactions.